How are the coordinating teachers trained in the state educational network of Sao Paulo? - Vera, Rebeca Franciele; Silva Fernandes, Maria Jose da [UNESP] (Univ Nove Julho, 2019)
The article problematizes the formative actions destined to coordinating teachers (PC) in the state education network of Sao Paulo. The data analyzed are based on a documentary survey on continuing education offered by the State Secretariat, especially by the School of Teacher Training (EFAP), from 2010 to 2018. Fragilities have been identified in the training actions directed at those who in the schools carry out the continuous training of teachers. There is a predominance of short duration actions, in the distance modality, organized in a traditional perspective and disarticulated of the collective pedagogical organization of the schools.
Keywords: Coordinating teachers; Continuing education; State Education network of Sao Paulo